Manly arts : masculinity and nation in early American cinema - Gerstner, David A., 1963- (e-Duke books scholarly collection., 2006)
Examines the anxieties of class and race and the conflicts between New and Old Worlds that attend the elevation of masculinity as a defining characteristic of early American cinema and visual culture.